2021
DOI: 10.1111/cpr.13075
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotics ameliorate alveolar bone loss by regulating gut microbiota

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 86 publications
4
41
1
Order By: Relevance
“…Estrogen-deficient mice exhibited pathological bone loss and impaired bone microarchitecture in femur, with downregulated gut epithelial TJ protein expression and increased serum endotoxin levels, and these pathologies could be prevented by probiotics administration ( Li J. Y. et al., 2016 ). Consistently, our previous studies observed enhanced gut permeability, elevated serum LPS, and systemic inflammation in OVX mice, consequently resulting in Th17-related immune responses in alveolar bone and aggravated periodontitis ( Jia et al., 2019 ; Jia et al., 2021 ). In addition, administration of probiotics or berberine increased gut butyrate-producing bacteria, enhanced gut barrier function with reduced circulating LPS, and thus ameliorated estrogen deficiency-induced alveolar bone loss ( Jia et al., 2019 ; Jia et al., 2021 ).…”
Section: Underlying Mechanisms Of Gut-alveolar Bone Axissupporting
confidence: 90%
See 3 more Smart Citations
“…Estrogen-deficient mice exhibited pathological bone loss and impaired bone microarchitecture in femur, with downregulated gut epithelial TJ protein expression and increased serum endotoxin levels, and these pathologies could be prevented by probiotics administration ( Li J. Y. et al., 2016 ). Consistently, our previous studies observed enhanced gut permeability, elevated serum LPS, and systemic inflammation in OVX mice, consequently resulting in Th17-related immune responses in alveolar bone and aggravated periodontitis ( Jia et al., 2019 ; Jia et al., 2021 ). In addition, administration of probiotics or berberine increased gut butyrate-producing bacteria, enhanced gut barrier function with reduced circulating LPS, and thus ameliorated estrogen deficiency-induced alveolar bone loss ( Jia et al., 2019 ; Jia et al., 2021 ).…”
Section: Underlying Mechanisms Of Gut-alveolar Bone Axissupporting
confidence: 90%
“…Consistently, our previous studies observed enhanced gut permeability, elevated serum LPS, and systemic inflammation in OVX mice, consequently resulting in Th17-related immune responses in alveolar bone and aggravated periodontitis ( Jia et al., 2019 ; Jia et al., 2021 ). In addition, administration of probiotics or berberine increased gut butyrate-producing bacteria, enhanced gut barrier function with reduced circulating LPS, and thus ameliorated estrogen deficiency-induced alveolar bone loss ( Jia et al., 2019 ; Jia et al., 2021 ). Estrogen is potentially an important modulator of gut barrier.…”
Section: Underlying Mechanisms Of Gut-alveolar Bone Axissupporting
confidence: 90%
See 2 more Smart Citations
“…Probiotic Akkermansia muciniphila was revealed to reduce gingipain transcription by P. gingivalis , thereby decreasing inflammatory cell infiltration and alleviating alveolar bone loss ( Huck et al., 2020 ). Recently, we discovered that administration of probiotics enriched butyrate-producing genera of gut microbiota, improved intestinal barrier function, and decreased gut permeability, thus preventing inflammatory alveolar bone resorption in ovariectomized rats ( Jia et al., 2021 ).…”
Section: Factors That Affect Oral Microbiota-mediated Alveolar Bone Metabolismmentioning
confidence: 99%